Influence of Short-Form Video Content on Impulse Buying Behaviour Among Gen Z Consumers in Puducherry Region (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid growth of short-form video platforms such as Instagram Reels, YouTube Shorts, and TikTok-style applications has significantly transformed consumer engagement and online shopping behaviour among Gen Z consumers. These platforms utilize entertaining, visually appealing, and highly personalized content that can strongly influence consumer emotions and purchase decisions. This study examines the influence of short-form video content on impulse buying behaviour among Gen Z consumers in the Puducherry region. The research focuses on key factors such as entertainment value, influencer credibility, Fear of Missing Out (FOMO), social media engagement, and perceived enjoyment in shaping impulsive purchasing decisions. A structured questionnaire-based survey method is proposed to collect primary data from Gen Z consumers who actively use short-form video platforms. The study aims to identify the extent to which exposure to short-form videos triggers unplanned purchases and alters consumer decision-making patterns. The findings are expected to provide valuable insights for digital marketers, e-commerce businesses, and social media advertisers in developing effective marketing strategies targeting young consumers. Furthermore, the study contributes to the growing body of literature on digital consumerism and emerging social media marketing trends in regional markets.